2014
DOI: 10.1175/jcli-d-14-00113.1
|View full text |Cite
|
Sign up to set email alerts
|

Southern Hemisphere Cloud–Dynamics Biases in CMIP5 Models and Their Implications for Climate Projections

Abstract: This study quantifies cloud-radiative anomalies associated with interannual variability in the latitude of the Southern Hemisphere (SH) midlatitude eddy-driven jet, in 20 global climate models from phase 5 of the Coupled Model Intercomparison Project (CMIP5). Two distinct model types are found. In the first class of models (type I models), total cloud fraction is reduced at SH midlatitudes as the jet moves poleward, contributing to enhanced shortwave radiative warming. In the second class of models (type II mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 46 publications
8
86
1
Order By: Relevance
“…The L-only fingerprint F(L) is increasingly apparent in both observational datasets and is incompatible with internal variability. We note, however, that several authors have suggested that cloud shifts may not be trivially related to changes in the jet (Grise and Polvani 2014;Ceppi et al 2014;Kay et al 2014), and further study of the interaction between clouds and the circulation is necessary to understand this response. This is in agreement with previous studies that suggest models fail to capture the observed poleward expansion (Johanson and Fu 2009;Seidel et al 2008).…”
Section: A Observed Poleward Migration Incompatible With Forced Modelsmentioning
confidence: 86%
“…The L-only fingerprint F(L) is increasingly apparent in both observational datasets and is incompatible with internal variability. We note, however, that several authors have suggested that cloud shifts may not be trivially related to changes in the jet (Grise and Polvani 2014;Ceppi et al 2014;Kay et al 2014), and further study of the interaction between clouds and the circulation is necessary to understand this response. This is in agreement with previous studies that suggest models fail to capture the observed poleward expansion (Johanson and Fu 2009;Seidel et al 2008).…”
Section: A Observed Poleward Migration Incompatible With Forced Modelsmentioning
confidence: 86%
“…Yoshida and Ishikawa, 2013). Even for the dynamical storm track, which may be thought satisfactorily resolved by low-resolution climate models, its bias in latitudinal position is related to the cloud amount bias in CMIP5 models (Grise and Polvani, 2014). Existing high-resolution atmosphere simulations suggest that the characteristics of the jet stream (Hodges et al, 2011) and blocking (Jung et al, 2012) will be improved by higher resolution.…”
Section: Scale Interactionsmentioning
confidence: 99%
“…But the myriad ways in which clouds couple to the storm tracks are just beginning to be appreciated, for instance through their radiative effects. As the clouds embedded within the storm tracks shift, there are systematic implications for the radiation budget and its influence on the temperature gradients that give rise to the storms in the first place 24,25 . The development of a hierarchy of modelling approaches is advancing understanding of how moist processes such as those embedded along frontal systems, interactions with ocean circulations, and cloud radiative effects influence both storm development and the structure of the storm tracks.…”
Section: Four Questionsmentioning
confidence: 99%